2000
DOI: 10.1002/1096-911x(20001201)35:6<608::aid-mpo25>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Loss of caspase‐8 expression in neuroblastoma is related to malignancy and resistance to TRAIL‐induced apoptosis

Abstract: Background and Procedures. NB-derived cell lines were tested for their sensitivity to apoptosis induced by the tumor-selective apoptotic ligand TRAIL. Noninvasive S-type cell lines are highly sensitive to TRAIL, whereas invasive N-type cell lines are resistant. Results. Although both S-and N-type cell lines express TRAIL-R2, FADD, and caspases-3 and -10, only S-type cells express caspase-8. Reduced levels of caspase-8 protein were also observed in a stage IV NB tumor when compared to a ganglioneuroma. The casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 11 publications
4
40
1
Order By: Relevance
“…However, other reports have indicated that several neuroblastoma cell lines are resistant to TRAIL-induced apoptosis. 26 Variation among neuroblastoma cell lines in sensitivity to TRAIL may be due to differences in expression levels of certain components of the TRAIL pathway. 27 For example, several neuroblastoma tumors and cell lines fail to express caspase-8.…”
Section: Delivery Of Trail Via An Adenoviral Vector Induces Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, other reports have indicated that several neuroblastoma cell lines are resistant to TRAIL-induced apoptosis. 26 Variation among neuroblastoma cell lines in sensitivity to TRAIL may be due to differences in expression levels of certain components of the TRAIL pathway. 27 For example, several neuroblastoma tumors and cell lines fail to express caspase-8.…”
Section: Delivery Of Trail Via An Adenoviral Vector Induces Apoptosismentioning
confidence: 99%
“…27 For example, several neuroblastoma tumors and cell lines fail to express caspase-8. 28 Alternatively, the differences in sensitivity may be due to epigenetic factors, such as the methylation of caspase-8, 26,28,29 which may substantially alter the ability of TRAIL to induce apoptosis. However, lack of TRAIL receptor expression prevented 27 suggesting that integrity of the entire TRAIL pathway is necessary for its function.…”
Section: Delivery Of Trail Via An Adenoviral Vector Induces Apoptosismentioning
confidence: 99%
“…In the present study we investigated the mechanism of dox-induced death in N-type NB cell lines LAN-1 and IMR-32, which are silenced for caspase-8 expression, amplified for N-myc, and are completely resistant to TNF-related apoptosis inducing-ligand (TRAIL)-induced death (Hopkins-Donaldson et al, 2000). We also assessed the role of the death receptor pathway in dox-induced death of the S-type NB cell line SH-EP used previously by Fulda et al (1998) which are highly sensitive to TRAIL-induced death (Hopkins-Donaldson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We also assessed the role of the death receptor pathway in dox-induced death of the S-type NB cell line SH-EP used previously by Fulda et al (1998) which are highly sensitive to TRAIL-induced death (Hopkins-Donaldson et al, 2000). Cell viability tests were performed in order to compare the sensitivity to dox-induced death of N-type and S-type NB cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The other four cell lines show differential patterns of loss. The primers and experimental conditions were as described before (Griffith et al, 1998;Hopkins-Donaldson et al, 2000;Ng et al, 1999;O'Connell et al, 1996). (b) Re-expression of CASP and CASP10 as demonstrated by RT -PCR after Aza-CdR treatment (Shivapurkar et al, 2002).…”
mentioning
confidence: 99%